THE EFFECTS OF USING CAKE APPLICATION TO IMPROVE LISTENING ABILITY OF THE TENTH GRADE STUDENTS OF STATE SENIOR HIGH SCHOOL 2 OF TUNGKAL JAYA - Desanti Putri; Djunaidi Djunaidi; Yus Vernandes Uzer (Esteem Journal of English Education Study Programme, 2023)
The objective of the researcher was to find out whether there was any significant effect toward the students who were taught listening using the cake application of the tenth-grade students of state senior high school 2 ofÂ  Tungkal Jaya.Â The population in this study was all class X for the academic year 2021/2022 . The total population was 153 students from 5 classes . The sample consists of students taken from classes X MIA 1 and X MIA 3 using purposive sampling . A quasi - Experimental design with Nanequvalent control group design pre - test and post - test was used in this study . In collecting the data , the researcher used a written test , and then the data was analyzed using normality , homogeneity , and a t - test . The homogeneity test score for the pre-test and post-test experiments was 0.214. The normality test was more significant than 0.05, Furthermore , the calculation result of the compatibility t - test was 2,322 , which was higher than the critical value of t - table 1.71, The null hypothesis (Ho) was rejected, while the alternative hypothesis (Ha) was accepted. Meaning that there was a significant effect toward the students who taught listening using the cake application of Tungkal Jaya and those who were not.